2021
DOI: 10.3390/ma14237395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dense MgB2 Superconductor via In Situ and Ex Situ Spark Plasma Sintering Method

Abstract: In this study, high-density magnesium diboride (MgB2) bulk superconductors were synthesized by spark plasma sintering (SPS) under pressure to improve the field dependence of the critical current density (Jc-B) in MgB2 bulk superconductors. We investigated the relationship between sintering conditions (temperature and time) and Jc-B using two methods, ex situ (sintering MgB2 synthesized powder) and in situ (reaction sintering of Mg and B powder), respectively. As a result, we found that higher density with supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(53 reference statements)
0
11
0
2
Order By: Relevance
“…To address these issues, various techniques have been developed to enhance the effective pinning sites in MgB 2 , such as irradiation, chemical doping or substitution, precursor size refinement, and other methods [2,3]. Additionally, highly dense bulk MgB 2 samples can be elaborated through infiltration and growth process [4,5], hot pressing or hot isostatic pressing sintering [6,7] and spark plasma sintering (SPS) [8][9][10]. SPS is an unconventional rapid consolidation method that allows for the preparation of dense samples with complex shapes and/or large sizes.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, various techniques have been developed to enhance the effective pinning sites in MgB 2 , such as irradiation, chemical doping or substitution, precursor size refinement, and other methods [2,3]. Additionally, highly dense bulk MgB 2 samples can be elaborated through infiltration and growth process [4,5], hot pressing or hot isostatic pressing sintering [6,7] and spark plasma sintering (SPS) [8][9][10]. SPS is an unconventional rapid consolidation method that allows for the preparation of dense samples with complex shapes and/or large sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In the 'in-situ' method, precursor materials are mixed in a stoichiometric ratio and heat-treated in an inert environment to react into the MgB 2 bulk of a desired form. Conversely, the 'ex-situ' approach utilizes pre-produced MgB 2 powders to shape the desired forms [39]. 'Ex-situ' procedures offer the advantage of producing homogeneous materials with dense inner cores due to the use of already reacted MgB 2 powders.…”
Section: Production Techniques Of Mgbmentioning
confidence: 99%
“…Additionally, the sintering productivity is low, and doping during the procedure is ineffective compared to 'in-situ' methods. Previous studies have shown that critical current density (J c ) in MgB 2 can be enhanced by various means, such as reducing grain size, carbon doping, incorporating additives, and introducing MgO nanoparticles in moderate quantities [36,38,39]. Increasing the density of grain boundaries by refining the precursors through high-energy planetary ball milling serves as a source of pinning centres, resulting in an increased J c [40,41].…”
Section: Production Techniques Of Mgbmentioning
confidence: 99%
“…These characteristics make MgB 2 highly advantageous for a wide range of applications including electric engines for planes, ships and spaceships as well as for the magnetic levitation of MAGLEV trains. The frequently used techniques to prepare MgB 2 bulks involve the spark plasma sintering (SPS) [14], hot pressing or isostatic pressing (HP/HIP) [15] and infiltration and growth process (IG) [16]. Perini et al [16][17][18] have successfully fabricated a large size MgB 2 square sample with an edge length of 117 mm and a thickness of 10 mm using reactive liquid Mg infiltration.…”
Section: Introductionmentioning
confidence: 99%